2000
DOI: 10.1021/ja002820h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structures, and Reactivity of Weakly Coordinating Anions with Delocalized Borate Structure:  The Assessment of Anion Effects in Metallocene Polymerization Catalysts

Abstract: The formation of adducts of tris(pentafluorophenyl)borane with strongly coordinating anions such as CN(-) and [M(CN)(4)](2)(-) (M = Ni, Pd) is a synthetically facile route to the bulky, very weakly coordinating anions [CN[B(C(6)F(5))(3)](2)](-) and [M[CNB(C(6)F(5))(3)](4)](2-) which are isolated as stable NHMe(2)Ph(+) and CPh(3)(+) salts. The crystal structures of [CPh(3)][CN[B(C(6)F(5))(3)](2)] (1), [CPh(3)][ClB(C(6)F(5))(3)] (2), [NHMe(2)Ph](2)[Ni[CNB(C(6)F(5))(3)](4)].2Me(2)CO (4b.2Me(2)CO), [CPh(3)](2)[Ni[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
150
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(162 citation statements)
references
References 58 publications
9
150
0
3
Order By: Relevance
“…[151 -153] Adducts formed by the coordination of anions such as CN - (64) and [Ni(CN) 4 ] 2-with B(C 6 F 5 ) 3 act as excellent activators for dialkylmetallocenes. [154,155] Very recently, an anion was reported having imidazole fragment 65 as the linking group. [156] The surprising observation that Al(C 6 F 5 ) 3 can abstract both methyl groups in dimethylmetallocene to form the dicationic bis(aluminate) complex 66 was brought to the attention by Chen et al [157] A 30-fold increase in catalytic activity was observed.…”
Section: Anion Engineeringmentioning
confidence: 99%
“…[151 -153] Adducts formed by the coordination of anions such as CN - (64) and [Ni(CN) 4 ] 2-with B(C 6 F 5 ) 3 act as excellent activators for dialkylmetallocenes. [154,155] Very recently, an anion was reported having imidazole fragment 65 as the linking group. [156] The surprising observation that Al(C 6 F 5 ) 3 can abstract both methyl groups in dimethylmetallocene to form the dicationic bis(aluminate) complex 66 was brought to the attention by Chen et al [157] A 30-fold increase in catalytic activity was observed.…”
Section: Anion Engineeringmentioning
confidence: 99%
“…However, a number of reports in the recent literature suggest that the choice of the anion can be important, both in terms of the structure of the salt and its reactivity. [1][2][3][4][5][6][7][8][9][10][11][12][13] Relevant examples include an anion dependence in 1) Diels-Alder catalysis, [1] 2) polymerization chemistry, [2] 3) catalytic hydrogenation, [3] 4) asymmetric ring opening reactions of oxabicyclic alkenes, [4] 5) asymmetric cyclopropanation, [5] and 6) C,H-activation reactions, [6] amongst others. The anions may or may not coordinate to the metal center.…”
Section: Introductionmentioning
confidence: 99%
“…11), and a weakly active titanocene catalyst at low temperature (114), respectively. Linked anionic structures such as (Ph 3 C)[(C 6 F 5 ) 3 B-CN-B(C 6 F 5 ) 3 ] are competent metallocene activators (115). Many other noncoordinating anions (116) have been discovered that enable high activity polymerization, including (C 6 F 5 ) 3 B-CN-B(C 6 F 5 ) 3 reactors, metallocene catalyst formulations nearly always comprise a solid support of well-controlled morphology and porosity (118).…”
Section: Discrete Activatorsmentioning
confidence: 99%